Sex differences in depression in Parkinson’s disease: cognitive dysfunction and female-specific associations - Zhao, Huashuo; Sun, Yi; Wang, Qiushuang; Zhao, Zixuan (Frontiers in Neuroscience, 2025)
ObjectiveThis study used a linear mixed model to explore the relationship between cognitive function and depression in Parkinson’s disease (PD) patients.ParticipantsThe study data were collected from 450 Parkinson’s disease patients who participated in the Parkinson’s Disease Progress Marker Project (PPMI) from 2010 to 2024, including 176 women and 274 men.MeasurementsCognitive function was assessed using the Montreal Cognitive Assessment Scale (Moca), and depression was measured using the Geriatric Depression Scale (GDS). The correlation between cognitive function and depression was determined using a linear mixed model.ResultsAnxiety, daily living ability, and autonomic nervous system function are significant factors affecting both men and women. Women experience a stronger impact of anxiety, daily activity limitations, and autonomic nervous system dysfunction on depression. The longer the duration of the illness, the more severe the depression in women. Moreover, cognitive abilities protect against depression only in women. Women exhibit higher individual heterogeneity in baseline depression and greater variability in the rate of change over time, with those who are more depressed showing a more gradual change.ConclusionIn female Parkinson’s disease patients, there is a negative correlation between cognitive ability and depression, whereas this correlation is not observed in male patients. This study provides new evidence that sex differences influence the relationship between cognitive ability and depression in Parkinson’s disease patients. Future research should consider the role of sex differences in the context of cognitive ability and depression.